Determination of Lead Acetate Effects on Heavy Weight Protein of Musca domestica - Rizwanul Haq, (Journal of Basic & Applied Sciences, 2013)
So many insects are influenced easily by many pollutants; therefore, the influence of lead (as lead acetate) on Musca domestica was studied,lead is considered to be an important toxic waste which could contaminate the environment, such as soil, air and water, therefore, insects could be influenced by the lead. Musca domestica, was studied at 48 hours post treatment, under the effects of lead acetate, in different concentrations. Thus the lead is found to exert a definite specific physiological and morphological effect on these flies, It was observed that under the effects of lead abnormalities and deformity were developed in the larvae of flies. Thus these flies could present a useful module for the quick transmission of the environmental hazards due to lead contamination, which exerts a specific physiological and morphological effect on these flies. The purpose of the present work was to determin the effects of lead on proteins as a major indicator of physiological features alongwith morphology features of larvae of Diptera flies.